Depression and Nigral Neuron Density in Lewy Body Spectrum Diseases - Saari Laura; Heiskanen Lauri; Gardberg Maria; Kaasinen Valtteri (WILEY, 2025)
Parkinson's disease and other Lewy body spectrum diseases (LBDs) are associated with a specific risk for clinical depression. In the present clinicopathological study with 73 patients with LBD, we observed that the substantia nigra pars compacta dopamine neuron density was markedly lower in patients who had comorbid depression antemortem than in nondepressed patients (1.52 vs 2.32 n/mm(2), p = 0.004). There were no differences in cognition, motor disease severity, antiparkinsonian medications, or disease duration between groups. The results implicate the substantia nigra as an important psychomotor modulatory area of mood in patients with Lewy body disorders. ANN NEUROL 2021